Family of fast jacket transform algorithms - Lee, M.; Zeng, G. (Electronics letters, 2007)
A family of fast Jacket transform algorithms that have identical stage factorisations is presented by making use of suitable permutation matrices. The proposed algorithms are faster than the conventional Jacket transforms.